Numerical modelling of the human arterial network in conjunction with the GTF technique to improve cardiovascular diagnostics - Butt, Ahmed Tamkin (2019)
The argument on the effectiveness of the Generalized Transfer Function (GTF) technique is currently ongoing. To resolve the dispute in experiment based studies, this thesis aims to use a well-validated numerical model as an alternative to experimental studies to test the validity of the GTF method. This thesis divides the work into four main inter-disciplinary areas of research.